PELATIHAN KONSELOR SEBAYA UNTUK PENCEGAHAN HIV/ AIDS PADA SISWA SMP NEGERI 35 PADANG - Melisa Yenti; Shabrina Erika; Afifah Syabrina Safli; Andama Rizky Maulana; Leny Chania Putri; Najla Giva Tsuraya; Rahmad Fadhil Caesario (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
There has been an increase in the number of adolescents aged 15-24 worldwide infected with HIV. A comprehensive understanding of HIV-AIDS is crucial in improving access to HIV services and bringing about behavioral changes to reduce risks. Early prevention through health education is important to curb HIV/AIDS cases. Specifically, peer counselor training for HIV/AIDS has not been conducted at SMPN 35 Padang, hence the necessity for such training. The objective of this activity is to enhance the knowledge of peer counselors regarding HIV/AIDS so that they can effectively counsel their peers. The activity will take place at SMP Negeri 35 Padang, specifically in Seberang Padang, Padang Selatan Sub-district, Padang City. Methods employed in this activity include guidance and counseling, brainstorming, games, practicing using health promotion media, and group discussions. Twenty-three peer counselor participants will undergo this training. The outcome of the training indicates an increase in the knowledge of peer counselors regarding HIV/AIDS prevention at SMPN 35 Padang. Before the training (pre-test), the average knowledge level was 6.57, and after the training (post-test), it rose to 9.13, with a p-value of 0.000. This demonstrates the effectiveness of peer counselor education through training in enhancing their knowledge about HIV/AIDS. It is hoped that peer counselors will fulfill their roles by providing information on HIV/AIDS prevention to their peers at school.